Index: The Book of Statistical ProofsStatistical Models ▷ Count data ▷ Binomial observations ▷ Maximum likelihood estimation

Theorem: Let $y$ be the number of successes resulting from $n$ independent trials with unknown success probability $p$, such that $y$ follows a binomial distribution:

$\label{eq:Bin} y \sim \mathrm{Bin}(n,p) \; .$

Then, the maximum likelihood estimator of $p$ is

$\label{eq:Bin-MLE} \hat{p} = \frac{y}{n} \; .$

Proof: With the probability mass function of the binomial distribution, equation \eqref{eq:Bin} implies the following likelihood function:

$\label{eq:Bin-LF} \begin{split} \mathrm{p}(y|p) &= \mathrm{Bin}(y; n, p) \\ &= {n \choose y} \, p^y \, (1-p)^{n-y} \; . \end{split}$

Thus, the log-likelihood function is given by

$\label{eq:Bin-LL} \begin{split} \mathrm{LL}(p) &= \log \mathrm{p}(y|p) \\ &= \log {n \choose y} + y \log p + (n-y) \log (1-p) \; . \end{split}$

The derivative of the log-likelihood function \eqref{eq:Bin-LL} with respect to $p$ is

$\label{eq:dLL-dp} \frac{\mathrm{d}\mathrm{LL}(p)}{\mathrm{d}p} = \frac{y}{p} - \frac{n-y}{1-p}$

and setting this derivative to zero gives the MLE for $p$:

$\label{eq:p-MLE} \begin{split} \frac{\mathrm{d}\mathrm{LL}(p)}{\mathrm{d}\hat{p}} &= 0 \\ 0 &= \frac{y}{\hat{p}} - \frac{n-y}{1-\hat{p}} \\ \frac{n-y}{1-\hat{p}} &= \frac{y}{\hat{p}} \\ (n-y) \, \hat{p} &= y \, (1-\hat{p}) \\ n \, \hat{p} - y \, \hat{p} &= y - y \, \hat{p} \\ n \, \hat{p} &= y \\ \hat{p} &= \frac{y}{n} \; . \end{split}$
Sources:

Metadata: ID: P381 | shortcut: bin-mle | author: JoramSoch | date: 2022-11-23, 18:17.